Let x and y be positive reals satisfying x 2 + y 2 = 1 8 , find the maximum of x + y .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
N i c e O b s e r v a t i o n
By AM-GM Inequality,
2 x 2 + y 2 ≥ x 2 y 2 9 ≥ x y
So maximum value, x + y = x 2 + y 2 + 2 x y = 3 6 = 6
nice!!!!!!
Can also be solved by considering a point on the circle x^2+y^2=18 in first quadrant which gives x+y=3root2(sint+cost) giving max value=6
i solved with c-s. but i am going to use derivatives here just for the sake of variety. since x is positive: x = 1 8 − y 2 the required f ( y ) = y + x = y + 1 8 − y 2 for the max(or min) to be achieved, f'(y)=0. f ′ ( y ) = 1 + ( − y ) ( 1 8 − y 2 ) − 1 = 0 1 8 − y 2 = y y 2 = 9 ⟹ y = 3 the max is f ( 3 ) = 6 we check this indeed is max by substituting say y=1.
This is a straightforward application of a two variable case of QA inequality . For proof , see the first example in the wiki. Substitute required values and we get x + y ≤ 6 .
C O O L ! !
We can use the QM-AM inequality which states that 2 x 2 + y 2 ≥ 2 x + y . Now it's given that x 2 + y 2 = 1 8 .Substituting this in this inequality,we get 2 1 8 ≥ 2 x + y ∴ 6 ≥ x + y .
N I C E ! !
(X^2+y^2)^1/2=(2×3×3)^1/2
×+y=2×3 =6
you need to improve a lot..., start with x 2 + y 2 = ( x + y ) 2 try 1,2 to confirm, x 2 + y 2 + 2 x y = ( x + y ) 2 also, 2 ∗ 3 2 = 3 2 = 2 ∗ 3 = 6 search our wikis "rules of exponent"
x 2 + y 2 = 1 8 represents a circle of radius equal to 1 8 and let value of x + y = k the for maximum value the line x + y = k should be tangent to circle so its perpendicular distance from origin is equal to the radius of circle i.e 1 8 which on solving gives value of k as 1 2 + 1 2 ∣ 0 + 0 − k ∣ = 1 8 therefore we get k = 6
Problem Loading...
Note Loading...
Set Loading...
Using Cauchy-Schwartz inequality, we have:
( x + y ) 2 ⇒ x + y ≤ ( 1 + 1 ) ( x 2 + y 2 ) = 3 6 x 2 + y 2 = 1 8 ≤ 6